Impact of Integrated Ultra Violet-Ozone Treatment on Textural and Structural Properties of Dough Made of Natural Fiber Based Agro Residues. Issue 1 (31st December 2023) - Harikrishnan, M.P.; Vishnu, V.; Kothakota, Anjineyulu; Pandiselvam, R.; Venkatesh, T.; Pillai, Saju; Manikantan, M.R.
ABSTRACT: In this study, de-oiled rice bran (RB) and virgin coconut oil cake (VCOC) were selected as base materials. Corn starch, wheat bran, and guar gum were taken as binding agents. The doughs were treated with combined Ultraviolet (UV) (1000 μW/cm2 for 15 min) and Aqueous Ozone (AO) (3 mg/L, exposure time 5 min and pH of 4). The effect of these non-thermal treatments on microbial log reduction, textural characteristics, glass transition (Tg), and crystallinity was studied and compared with the control. The results for all samples, dough raising capacities differed widely by 10–30%. Bulk Density and True Density were 1.6 to 2.5 g/cm3 and 2.3 to 3.3 g/cm3. X-Ray Diffraction indicated 30–45% crystallinity, and crystallite size ranges between 0.54 and 0.90 nm. DSC indicated Tg and melting point between 49°C-55°C and 98°C-101°C for RB dough and at 54°C-60°C and 107°C-134°C for VCOC dough samples. UV with AO treated dough showed a maximum of 5.2 log microbial reduction compared to the untreated sample. The developed RB and wheat bran combination demonstrated the highest tensile strength (0.62 MPa) whereas RB-starch combination had the minimum water absorption (1.33 ml/min). This indicates the ability of additives to improve the characteristics of biodegradable cutlery made from agricultural residues. GRAPHICAL ABSTRACT: uf0001